In the studio : visual creation and its material environments - Jacobson, Brian R. (University of California Press, 2020)
"Studios are, at once, material environments and symbolic forms, sites of artistic creation and physical labor, and nodes in networks of resource circulation. They are architectural places that generate virtual spaces-worlds built to build worlds. On the outside, they have become icons of corporate identity, while on the inside, they have remained invisible in order to be seen. As such, they have actively faded into the background of critical discourse and into the margins of film and media history. Recovering their hidden role in the history of visual creation, In the Studio demonstrates that when we foreground these worlds, we gain new insights into moving-image culture and the material, ecological, social, political, and economic dynamics that quietly mark the worlds on our screens. Spanning the twentieth century and moving globally, from Japan to Brazil, Mexico to Moscow, and Hollywood to Dubai, this unique collection tells new stories about studio icons--Pinewood, Cinecittà, Churubusco, and CBS--as well as the experimental workplaces of filmmakers and artists from Aleksandr Medvedkin to Charles and Ray Eames and Hollis Frampton"--